Selective Regulation of Oocyte Meiotic Events Enhances Progress in Fertility Preservation Methods - Celik, Onder; Celik, Nilufer; Gungor, Sami; Haberal, Esra Tustas; Aydin, Suleyman (Sage Publications Ltd, 2015)
Following, early embryonic germ cell migration, oocytes are surrounded by somatic cells and remain arrested at diplotene stage until luteinizing hormone (LH) surge. Strict regulation of both meiotic arrest and meiotic resumption during dormant stage are critical for future fertility. Intercellular signaling system between the somatic compartment and oocyte regulates these meiotic events and determines the follicle quality. As well as the collected number of eggs, their qualities are also important or in vitro fertilization (IVF) outcome. In spontaneous and IVF cycles, germinal vesicle (CV) stage oocytes, premature CV breakdown, and persistence of first meiotic arrest limit the reproductive performance. Likewise, both women with premature ovarian aging and young cancer women are undergoing chemoradiotherapy under the risk of folliele loss because of unregulated meiotic events. Understanding of oocyte meiotic events is therefore critical for the prevention of functional ovarian reserve. High levels of cyclic guanosine monophophate (cCMP), cyclic adenosine monophophate (cAMP) and low phosphodiesterase (PDE) 3A enzyme activity inside the oocyte are responsible for maintaining of meiotic arrest before the LH surge. cGMP is produced in the somatic compartment, and natriuretic peptide precursor C (Nppc) and natriuretic peptide receptor 2 (Npr2) regulate its production. cGMP diffuses into the oocyte and reduces the PDE3A activity, which inhibits the conversion of cAMP to the 5'AMP, and cAMP levels are enhanced. In addition, oocyte itself has the ability to produce cAMP. Taken together, accumulation of cAMP inside the oocyte induces protein kinase activity, which leads to the inhibition of maturation-promoting factor and meiotic arrest also continues. By stimulating the expression of epidermal growth factor. LH inhibits the Nppc/Npr2 system, blocks cCMP synthesis, and initiates meiotic resumption. Oocytes lacking the functional of this pathway may lead to persistence of the GV oocyte, which reduces the number of good quality eggs. Selective regulation of somatic cell signals and oocyte meiotic events enhance progress in fertility preservation methods, which may give us the opportunity to prevent follicle loss in prematurely aging women and young women with cancer are undergoing chemoradiotherapy.
Keywords: oocyte meiosis; fertility preservation; cGMP; cAMP; PDEs; Nppc/Npr2